The conceptus regulates tryptophanyl-tRNA synthetase and superoxide dismutase 2 in the sheep caruncular endometrium during early pregnancy. (March 2015) - Al-Gubory, K.H.; Arianmanesh, M.; Garrel, C.; Fowler, P.A.
Abstract: Conceptus-derived paracrine signals play crucial roles in the preparation of a uterine environment capable of supporting implantation and development of the conceptus. However, little is known about the regulation of endometrial tryptophanyl tRNA synthetase (WARS) and manganese superoxide dismutase (SOD2) protein expression by the implanting and post-implanting conceptus. We hypothesized that the conceptus-derived signals favourably influences uterine environment for implantation through regulation of WARS and SOD2 expression in ovine caruncular endometrium. To test this hypothesis, WARS and SOD2 protein and mRNA expression was determined in caruncular endometrial tissues of unilaterally pregnant ewes at implantation (day 16) and post-implantation (day 20) periods. WARS protein expression increased in caruncular tissues of the gravid uterine horns compared with the non-gravid uterine horns on days 16 and 20 of pregnancy. There were no changes in SOD2 protein expression between the gravid and non-gravid uterine horns, irrespective of the day of pregnancy. On day 16 of pregnancy, there were no differences in WARS and SOD2 mRNA expression between the gravid and non-gravid uterine horns but expression of both genes was higher in the gravid uterine horns when compared with the non-gravid uterine horns on day 20 of pregnancy. In conclusion, the use of the unilaterally pregnant ewe model provides for the first time firm evidence that the early implantation and post-implanting conceptus-derived signals up-regulate WARS protein expression within the caruncular endometrium. Further studies are necessary to identify these signalling molecules and to understand mechanisms whereby they exert paracrine action within the endometrium.